Transferência térmica conjugada utilizando fronteira imersa para solução de problemas bidimensionais - Santos, Gabriel Machado dos (2022)
Problems of thermo-fluid-structural interaction, or conjugate heat transfer, correspond to the class of physical phenomena in which heats effects alter the dynamics of fluid-structural coupling. These problems are characterized by a continuous exchange of thermal energy between the solid structure and the flow, so that conventional thermal boundary conditions are not applicable to the fluid-solid interface, requiring the use of heat couplings. Extensive are the natural or industrial phenomena involving conjugated heat interactions between flow and structure, and depending on the purpose of the intended application, their effects can be potentiated or minimized. Technological advances in the field of engineering require the manufacture of equipment and machines with increasingly better cooling and/or insulation capabilities. Thus, the structural and fluid dynamic design of these equipments must be designed aiming at the thermal interaction between flow and structure. Thus, the search and interest in tools that enable the analysis and study of these problems is growing, where virtual experimentation based on numerical-computational methodology has been highlighted. Therefore, the present work aims at the physical, mathematical and computational modeling of conjugated heat transfer problems, in addition to the development of a computational code in Fortran 90 programming language, which is intended to deal with two-dimensional problems with the presence of a conductive solid body, making it necessary to apply the immersed boundary methodology. In the implementations carried out, the equations that model the dynamics, transport and energy transformation in the fluid subdomain are discretized and solved in a two-dimensional, eulerian, cartesian and fixed domain, through the finite difference method, where the fractional step method is used for pressure-velocity coupling. The equation that models the thermal energy balance in the solid subdomain is discretized and solved in a lagrangian domain, formed by triangular elements, using the finite element method. The immersed boundary methodology is applied in order to approach both subdomains in distinct and independent ways. The solutions obtained for each subdomain, individually, are coupled according to the strong partitioned coupling methodology. Verification tests are performed in order to verify the implementations performed. Simulations are carried out in order to validate the numerical-computational model developed, where the results obtained are in accordance with those presented in the literature.